Indeks Eritrosit sebagai Indikator Prognostik Anemia pada Pasien Gagal Ginjal Kronis dengan Hemodialisa di RSUD Bahteramas Provinsi Sulawesi Tenggara - Usman, Julianti Isma Sari; Anita Rosanty; Nurul Annisa Febriana Dahlan (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
Chronic kidney disease is a progressive and irreversible decline in kidney function, requiring hemodialysis therapy in the end stage. One of the most common complications is anemia, which can be assessed through erythrocyte indices, including MCV, MCH, and MCHC. This study aims to determine the value of the erythrocyte index as a prognostic indicator in patients with chronic kidney failure with hemodialysis. This research is a descriptive study with a cross-sectional approach. A total of 34 patients were selected using a purposive sampling technique. Blood samples were analyzed using a Sysmex XN-1000 Hematology Analyzer. The results showed normocytic normochromic in 27 patients (79%), microcytic normochromic in 4 patients (12%), and microcytic hypochromic in 3 patients (9%). The average erythrocyte index in patients with chronic renal failure with hemodialysis was found to have an average MCV value of 86.2 fL, MCH 27.5 pg, MCHC 31.8% and hemoglobin 9.1 g/dl which indicates normocytic normochromic anemia. The conclusion of this study is that chronic kidney disease patients undergoing hemodialysis predominantly have normocytic normochromic erythrocyte indices.